Ángel Martínez Gutiérrez, Geographical origin and olive oils, Editoriale Scientifica, Napoli 2020 - Leśkiewic, Katarzyna (Przegląd Prawa Rolnego, 2021)
Ángel Martínez Gutiérrez, Geographical origin and olive oils, Editoriale Scientifica, Napoli 2020